2D RGO / Ag: ZnIn2S4 composite Z-type photocatalyst, application and exposed waterproof coiled material
By adding 2D RGO/AG: Znin2S4 composite optical catalyst at the exposed layer of the exposed SBS modified asphalt roll, solve the problem of roll surface pollution and rainwater erosion, achieve stronger self -cleaning and oxidation reduction reduction Ability has extended the service life of the coils.
Patent Information
- Application Number
- CN202411343359.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-24
AI Technical Summary
The existing exposed SBS modified asphalt waterproof coils are easily contaminated and eroded by rainwater on the exposed surface, and the semiconductor photocatalyst has a narrow photoresponse range, low efficiency of photogenerating carriers, and poor stability, which affects its photocatalytic activity.
The 2D RGO/AG: Znin2S4 composite Z -type photocatalyst is synthesized through the water thermal method, and the exposed layer of the waterproof coil is added. The oxidation and reduction capacity of the photocatalyst under the light is used to decompose pollutants and water attached to the exposed layer.
It improves the self-cleaning ability and redox ability of the exposed layer of the waterproof membrane, extends the service life of the membrane, and enhances the efficiency of the photocatalytic reaction.
Smart Images

Figure CN119346138A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of waterproofing coiled materials, and more specifically, relates to a 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst and its application and an exposed waterproofing coiled material. Background Art
[0002] Exposed SBS modified asphalt waterproofing membrane is popular in the market because of its high temperature resistance, convenient construction, short construction period and long-term exposure. However, at the same time, exposed membrane also has problems such as the exposed surface is easily contaminated by foreign pollutants (such as organic waste, dust, etc.) and the exposed layer is easily eroded by rain on rainy days.
[0003] Photocatalytic technology is a green technology that can utilize sunlight and is environmentally friendly. Its characteristics are mainly manifested in two aspects. First, semiconductor photocatalysts can convert solar energy into storable, pollution-free hydrogen energy. On the other hand, semiconductor photocatalysts can also use sunlight to degrade organic pollutants in the environment. The principle of photocatalytic technology is that photocatalysts produce substances with redox ability under light conditions, thereby achieving the purpose of purifying pollutants, synthesizing and converting substances. In addition, studies have shown that photocatalytic technology also has antibacterial, antiviral, self-cleaning and other functions. Therefore, photocatalytic technology is a green technology with important application prospects in both the energy and environmental fields.
[0004] After decades of research, people have been exploring semiconductor photocatalysts more and more deeply. It is found that in order to achieve industrialized production and be widely used in people's daily lives, some practical problems must be solved. For example, in the research, it was found that ① the light response range of semiconductor materials is narrow (that is, the band gap width Eg is small); ② the efficiency of photogenerated carriers is not high. In fact, only a small amount of e - (Electronics) and h + (holes) can participate in the photocatalytic reaction; ③ The poor stability of the prepared photocatalyst itself and other reasons have seriously affected the activity of the photocatalyst. In order to effectively solve this problem, people have designed and synthesized many stable and efficient semiconductor photocatalysts, among which composite photocatalysts have more efficient and stable catalytic ability. The reason is that when two different semiconductors come into contact with each other, a new electric field will be formed in the contact area, which is called a heterostructure. Heterostructures can effectively promote e - With h + The separation of photogenerated charge carriers and the migration rate of photogenerated charge carriers are greatly increased. Compared with single semiconductor photocatalysts, the heterostructure formed by composite photocatalysts has stronger photocatalytic activity.
[0005] Therefore, it is urgent to propose a new composite Z-type photocatalyst and an exposed waterproof membrane with the photocatalyst. Summary of the invention
[0006] The purpose of the present invention is to address the deficiencies of the prior art and to propose a 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst and its application and an exposed waterproofing membrane. The present invention adds a certain proportion of 2DRGO / Ag:ZnIn2S4 composite Z-type photocatalyst to the exposed layer of the waterproofing membrane, and under the action of light, pollutants and water attached to the exposed layer can be decomposed.
[0007] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst, wherein the composite Z-type photocatalyst is prepared by a hydrothermal method of oxidized graphene with water, AgNO3 aqueous solution, Zn(OAc)2 aqueous solution and In(OAc)3 aqueous solution in the presence of functional additives.
[0008] According to the present invention, preferably, the oxidized graphene (GO) is synthesized by the Hummers method, and the specific preparation process is as follows:
[0009] 1) Weigh potassium persulfate, phosphorus pentoxide and graphite powder in the ratio of 5:5:4, mix the three chemicals evenly, and transfer them to a 1000 mL three-necked flask.
[0010] 2) After setting up the mechanical stirring, heating and other devices and the three-necked flask containing the above-mentioned drugs, start the mechanical stirring and adjust the speed to 80rpm. Then slowly add concentrated H2SO4 to the three-necked flask. Add about 10mL for the first time. When the concentrated H2SO4 and the solid drugs become a paste under stirring, continue to slowly add 10mL of concentrated H2SO4 (smoke will occur at this time, let it release heat for a while before adding more), until the amount of concentrated H2SO4 added reaches about 40mL.
[0011] 3) The speed of mechanical stirring was increased to 130 rpm, and the oil bath was turned on for heating. The first heating temperature was adjusted to 40°C, and then the temperature was gradually raised to 80°C without further raising the temperature, and the reaction was stirred at this temperature for 10 hours. After the reaction was completed, it was cooled to room temperature and waited for processing.
[0012] 4) Prepare a 1000mL beaker and add 500mL of 80℃ distilled water into the beaker. Then slowly pour the product obtained by the reaction into the distilled water according to the principle of "small amounts and multiple times" and speed up the stirring speed. White smoke will come out at this time.
[0013] 5) Wash the sample with distilled water (using suction filtration) until the pH of the filtrate reaches 7, and then move it into an oven for drying (the oven temperature is set at 50°C).
[0014] 6) Using an ice-water bath, add 227 mL of concentrated H2SO4 to a 500 mL three-necked flask, weigh the above-mentioned dried sample, and weigh them in the mass ratio of 5:4:22.5 for the dried sample: sodium nitrate: potassium permanganate. Then mix the weighed dried sample with sodium nitrate and add them to the three-necked flask under stirring. At this time, the solution in the flask changes from colorless to black. Then divide the weighed KMnO4 into six equal parts. At this time, it is important to pay attention to the temperature of the solution in the flask to be controlled below 10°C. Under this condition, add all 6 parts of KMnO4 powder to the flask one by one within 1.5 hours. At this time, the solution gradually changes from black to grass green, accompanied by the appearance of small particles. Continue mechanical stirring for 30 minutes and transfer to the oil bath device.
[0015] 7) In an oil bath system, control the temperature to 35°C and react for one hour (during this process, the viscosity of the solution increases, the reaction becomes increasingly intense, bubbles are continuously generated, and it eventually turns into a brown paste). After the reaction is completed, let it stand for processing.
[0016] 8) Slowly pour the mixture to be treated into a beaker containing 700 mL of hot water at 70°C, and add the mixture to the beaker according to the principle of "small amounts and multiple times", and stir continuously to form a suspension. Then take 350 mL of 3% H2O2 and add it dropwise into the suspension, stirring while adding dropwise until the liquid turns bright yellow. After standing for several hours, the solution has stratification. Pour out the supernatant and centrifuge the remaining yellow viscous liquid for washing.
[0017] 9) During the washing process, first wash with 0.1 mol / L dilute HCl solution until no precipitation is produced by acidified BaCl2 detection. Then continue washing with deionized water until the pH of the supernatant in the centrifuge tube reaches 7. Finally, put the washed product into a watch glass and dry it at 50°C. The dried product is oxidized graphene (GO) (when oxidized graphene GO is compounded with Ag:ZnIn2S4 in the reactor, it will be reduced to reduced graphene RGO).
[0018] According to the present invention, preferably, based on the total weight of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst, the content of Ag:ZnIn2S4 is 30-50%.
[0019] According to the present invention, preferably, the functional aid comprises L-cysteine solution and thioacetamide solution;
[0020] The concentration of the L-cysteine solution is 0.05-0.15 mmol mL -1 ;
[0021] The concentration of the thioacetamide solution is 0.05-0.15 mmol mL -1 ;
[0022] The dosage ratio of the oxidized graphene, water, L-cysteine solution and thioacetamide solution is (90-110): (25-35): (25-30): (90-100) mg / mL / μL / μL.
[0023] According to the present invention, preferably, the preparation method of the composite Z-type photocatalyst comprises the following steps:
[0024] S1: mixing and stirring the oxidized graphene and water in the inner lining of a reactor to obtain a first mixed solution;
[0025] S2: Mixing the first mixed solution with AgNO3 aqueous solution, Zn(OAc)2 aqueous solution, In(OAc)3 aqueous solution and functional additives in the lining of the reactor to obtain a second mixed solution;
[0026] S3: placing the reactor lining containing the second mixed liquid into the reactor shell and performing heating, cooling, washing and drying treatments in sequence to obtain the composite Z-type photocatalyst.
[0027] In the present invention, the reactor lining is a polytetrafluoroethylene lining.
[0028] According to the present invention, preferably, the temperature of the heating treatment is 150-200° C. and the time is 22-30 hours.
[0029] According to the present invention, preferably, the drying treatment is carried out at a temperature of 45-55° C. and for a time of 10-15 hours.
[0030] In the present invention, as a preferred embodiment, the hydrothermal synthesis process of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst of the present invention is as follows:
[0031] S1: Weigh 100 mg of oxidized graphene into a 100 mL polytetrafluoroethylene liner, add 30 mL of deionized water, and use a suitable magnetic rotor to perform magnetic stirring for 30 minutes until GO is evenly dispersed in the water to obtain a first mixed solution;
[0032] S2: Use a pipette to accurately measure 17.4 μL of 0.8 mmol L -1 AgNO3 aqueous solution, 47.2μL 0.05mmolmL -1of Zn(OAc)2 aqueous solution and 472 μL 0.01 mmol mL -1 The In(OAc)3 aqueous solution was added to the polytetrafluoroethylene liner containing the first mixed solution, and then magnetically stirred for 10 minutes. Then 28.3 μL 0.1 mmol mL -1 94.4 μL 0.1 mmol mL -1 The thioacetamide solution (TAA) was added to the mixed system, stirred for 10 minutes, and the rotor was removed to obtain a second mixed solution.
[0033] S3: Place the polytetrafluoroethylene liner containing the second mixed solution into the reactor shell, and then heat it in an oven at 180°C for 24 hours. After cooling to room temperature, wash it with deionized water by centrifugation, and then dry it in an oven at 50°C for 12 hours. The dried product is the composite Z-type photocatalyst.
[0034] The second aspect of the present invention provides the use of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst as a material for preparing an exposed layer of an exposed waterproof membrane.
[0035] The third aspect of the present invention provides an exposed waterproofing membrane, the exposed waterproofing membrane comprising a substrate and an exposed layer coated on the upper surface of the substrate;
[0036] The materials of the exposed layer include sand particles and the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst.
[0037] According to the present invention, preferably, based on the total weight of the material of the exposed layer, the content of the sand particles is 95.0-99.9%, and the content of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst is 0.1-5.0%.
[0038] According to the present invention, preferably, the sand particles are shale flakes.
[0039] According to the present invention, preferably, the substrate comprises a tire base and a coating layer; the tire base, coating layer and exposed layer are arranged in sequence from bottom to top;
[0040] The tire base is a polyester tire base (PY);
[0041] The coating material layer comprises the following components by weight: 55-65 parts of base asphalt, 8-12 parts of SBS modifier, 3-10 parts of rubber powder filler and 15-25 parts of stone powder filler. Therefore, in the present invention, the exposed waterproofing membrane is an exposed SBS modified asphalt waterproofing membrane.
[0042] According to the present invention, preferably, the coating layer is prepared by uniformly mixing the base asphalt, SBS modifier, rubber powder filler and stone powder filler, and coating the mixture on the tire base. Preferably, the stirring temperature is 150-200°C, the stirring speed is 1500-2500r / min, and the stirring time is 2-3h.
[0043] In the present invention, the exposed layer is prepared by uniformly mixing the sand particles and the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst and coating the mixture on the coating layer. The exposed layer is uniformly coated on the coating layer and has good adhesion to the coating layer.
[0044] In the present invention, the exposed layer of the waterproof roll material with the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst added has a stronger self-cleaning ability than the exposed layer of the conventional waterproof roll material doped with a single RGO photocatalyst component. The reason is that: Figure 1 As shown, the light-induced e - (Electronics) and h + The movement of holes at the interface of RGO and Ag:ZnIn2S4 leads to the effective separation of charges between the two semiconductor materials. The transfer between them greatly slows down the e - and h + The recombination rate between them increases the efficiency of the photocatalytic reaction. Figure 2 As shown, the exposed layer of the waterproof roll with the addition of 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst can more efficiently remove organic pollutants, dust, etc. attached to its surface through light irradiation, so that the photocatalyst absorbs light energy and then undergoes redox reaction to achieve the purpose of decomposing organic pollutants, etc.; secondly, if the exposed layer of the waterproof roll encounters liquids such as water, the composite Z-type photocatalyst that absorbs light energy will more efficiently oxidize and decompose the water attached to the surface into hydrogen. Thereby achieving the purpose of reducing the time of water soaking the surface of the roll and extending the service life of the roll. In short, the exposed SBS modified asphalt waterproof roll with composite Z-type photocatalyst of the present invention has stronger self-cleaning ability and redox ability, which can improve the cleanliness of the surface of the roll and extend the service life of the roll.
[0045] In addition, the mechanism of action of the 2D WO3 / Ag:ZnIn2S4 composite Z-type photocatalyst in the prior art is different from the mechanism of action of the above-mentioned 2DRGO / Ag:ZnIn2S4 composite Z-type photocatalyst. The mechanism of action of the 2D WO3 / Ag:ZnIn2S4 composite Z-type photocatalyst is as follows: the electrons on the valence bands of WO3 and Ag:ZnIn2S4 migrate to their respective conduction bands under the illumination of light, but driven by the charge difference at the heterojunction interface, the photogenerated electrons on the conduction band of WO3 must recombine with the holes on the valence band of Ag:ZnIn2S4, thereby forming a "Z-type" photogenerated electron transport pathway, which effectively prolongs the migration path of the photogenerated carriers, thereby hindering the recombination of electron-hole pairs, and achieving the purpose of improving the photocatalytic effect. The effect of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst is different from that of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst of the present invention. The reason is that graphene, as a single substance, is a two-dimensional crystal composed of carbon atoms, and the arrangement of carbon atoms is consistent with the single atomic layer in graphite. Due to its own optical properties, it is stronger than the WO3 / Ag:ZnIn2S4 composite material based on oxide WO3. Although both are "Z" type composite structures, the photocatalytic effect of 2D RGO / Ag:ZnIn2S4 in the present invention is better than that of 2DWO3 / Ag:ZnIn2S4 composite Z-type photocatalyst as a whole.
[0046] The beneficial effects of the technical solution of the present invention are as follows:
[0047] The present invention successfully constructed 2D RGO / Ag:ZnIn2S4, a Z-type heterojunction composite (RGO is reduced graphene), i.e., a composite Z-type photocatalyst, by a hydrothermal method. The test results show that the Z-type heterojunction composite of the present invention exhibits better performance than pure sample RGO nanosheets in both photohydrolysis hydrogen production and photodegradation of organic pollutants, and has stronger self-cleaning ability. This is mainly attributed to the Z-type heterojunction composite of the present invention in situ loading Ag:ZnIn2S4 to form a unique Z-type heterojunction composite system, which prolongs the transmission path of photogenerated charges, thereby hindering the recombination of photogenerated charges, and enhancing the redox ability of photogenerated carriers, which can ultimately effectively improve the photocatalytic rate.
[0048] The present invention adds a certain proportion of Z-type heterojunction composites to the exposed layer of the waterproof coiled material, and utilizes the principle of the redox ability of the photocatalyst under light conditions to effectively remove organic pollutants on the surface of the exposed layer of the waterproof coiled material and water produced in rainy weather, thereby achieving the effect of cleaning the surface of the exposed layer of the waterproof coiled material and increasing the service life of the coiled material. It is worth mentioning that the Z-type heterojunction composite of the present invention has a stronger photocatalytic ability than that of a single RGO photocatalyst component.
[0049] The invention is environmentally friendly, does not require external energy and does not generate any pollution.
[0050] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0052] Figure 1 A reaction principle diagram of a 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst provided by the present invention is shown (A is reduced graphene (RGO), B is silver zinc indium thioate (Ag:ZnIn2S4), CB is the conduction band, and VB is the valence band).
[0053] Figure 2 A schematic diagram of photocatalysis of an exposed waterproof roll material provided by the present invention is shown.
[0054] The following are the descriptions of the reference numerals:
[0055] Substrate 1; exposed surface of substrate 2; shale sheet 3; 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst 4. DETAILED DESCRIPTION
[0056] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0057] In the following embodiments:
[0058] The model of base asphalt is 70#;
[0059] The mesh number of the rubber powder filler is 60 mesh;
[0060] The density of stone powder filler is 200 mesh;
[0061] SBS modifier was purchased from Beijing Yanshan Petrochemical Co., Ltd. of Sinopec Group.
[0062] The mesh number of shale flakes is 10 mesh.
[0063] Example 1
[0064] This embodiment provides a 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst, and the preparation method of the composite Z-type photocatalyst includes:
[0065] (1) Synthesis of oxidized graphene by Hummers method;
[0066] (2) Weigh 100 mg of oxidized graphene into a 100 mL polytetrafluoroethylene liner, add 30 mL of deionized water, and stir magnetically for 30 minutes using a suitable magnetic rotor until GO is evenly dispersed in the water to obtain a first mixed solution;
[0067] (3) Use a pipette to accurately measure 17.4 μL of 0.8 mmol L -1 AgNO3 aqueous solution, 47.2μL 0.05mmolmL -1 of Zn(OAc)2 aqueous solution and 472 μL 0.01 mmol mL -1 The In(OAc)3 aqueous solution was added to the polytetrafluoroethylene liner containing the first mixed solution, and then magnetically stirred for 10 minutes. Then 28.3 μL 0.1 mmol mL -1 94.4 μL 0.1 mmol mL -1 The thioacetamide solution (TAA) was added to the mixed system, stirred for 10 minutes, and the rotor was removed to obtain a second mixed solution.
[0068] (4) The polytetrafluoroethylene liner containing the second mixed solution is placed in the reactor shell, and then placed in an oven at 180°C for heating for 24 hours. After cooling to room temperature, it is centrifugally washed with deionized water, and then placed in an oven at 50°C for drying for 12 hours. The dried product is the 2DRGO / Ag:ZnIn2S4 composite Z-type photocatalyst.
[0069] Based on the total weight of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst, the content of Ag:ZnIn2S4 is 35%.
[0070] This embodiment also provides an exposed SBS modified asphalt waterproofing membrane, the exposed waterproofing membrane comprising a substrate and an exposed layer coated on the upper surface of the substrate, the substrate comprising a base and a coating layer, the base, coating layer and exposed layer being arranged in sequence from bottom to top;
[0071] The tire base is a polyester tire base (PY);
[0072] The coating material layer includes the following components by weight: 60 parts of base asphalt, 10 parts of SBS modifier, 5 parts of rubber powder filler and 20 parts of stone powder filler. The coating material layer is prepared by mixing the base asphalt, SBS modifier, rubber powder filler and stone powder filler uniformly and applying them on the tire base. The stirring temperature is 180°C, the stirring speed is 2000r / min, and the stirring time is 2.5h;
[0073] Based on the total weight of the materials of the exposed layer, the content of shale flakes is 99.5%, and the content of 2DRGO / Ag:ZnIn2S4 composite Z-type photocatalyst is 0.5%; the exposed layer is prepared by uniformly mixing shale flakes and the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst, coating the mixture on the coating layer, and naturally cooling the mixture.
[0074] Example 2
[0075] This embodiment provides an exposed SBS modified asphalt waterproof membrane. The only difference between this embodiment and Embodiment 1 is that, based on the total weight of the material of the exposed layer, the content of shale flakes is 99.0%, and the content of 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst is 1.0%.
[0076] Example 3
[0077] This embodiment provides an exposed SBS modified asphalt waterproofing membrane. The only difference between this embodiment and Embodiment 1 is that, based on the total weight of the material of the exposed layer, the content of shale flakes is 98.0%, and the content of 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst is 2.0%.
[0078] Test Case
[0079] This test example tests the exposed SBS modified asphalt waterproof membrane of each embodiment.
[0080] The 1# benchmark group is an exposed SBS modified asphalt waterproof membrane without photocatalyst doping;
[0081] The 2# control group was doped with an exposed SBS modified asphalt waterproofing membrane containing only RGO (reduced graphene) photocatalyst (
[0082] In the control group 1: based on the total weight of the exposed layer material, the content of shale flakes was 99.5%, and the content of RGO (reduced graphene) photocatalyst alone was 0.5%;
[0083] In control group 2: based on the total weight of the exposed layer material, the content of shale flakes was 99.0%, and the content of RGO (reduced graphene) photocatalyst alone was 1.0%;
[0084] In control group 3: based on the total weight of the exposed layer material, the content of shale flakes was 98.0%, and the content of only RGO (reduced graphene) photocatalyst was 2.0%;);
[0085] Experimental group 3# is the exposed SBS modified asphalt waterproofing membrane of Examples 1-3;
[0086] In order to visually observe the differences between the coils, we used 1% methyl orange solution as the target pollutant and deionized water as the target water reactant to conduct relevant tests. The specific test process is as follows:
[0087] Test 1:
[0088] (1) Take 1m of exposed coils of 1#, 2# and 3# respectively 2 , laid flat on the flat roof.
[0089] (2) Spray 20 mL of 1% methyl orange solution evenly on each exposed coil, and then use a stopwatch to time the time.
[0090] Test 2:
[0091] (1) Take 1m of exposed coils of 1#, 2# and 3# respectively 2 , laid flat on the flat roof.
[0092] (2) Spray 20 mL of deionized water evenly onto each exposed coil, and then use a stopwatch to time the time.
[0093] The test results are shown in Table 1.
[0094] Table 1
[0095]
[0096] The results in Table 1 show that:
[0097] The ability of the exposed coil of the present invention to degrade pollutants is much higher than that of the coil doped with a single photocatalyst RGO and the common exposed coil without adding a photocatalyst.
[0098] The ability of the exposed coiled material of the present invention to decompose deionized water is much higher than that of the coiled material doped with a single photocatalyst RGO and the common exposed coiled material without adding a photocatalyst.
[0099] The exposed coil of Example 2 has the best doping ratio.
[0100] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst, characterized in that: The composite Z-type photocatalyst is prepared by a hydrothermal method using oxidized graphene and water, AgNO3 aqueous solution, Zn(OAc)2 aqueous solution and In(OAc)3 aqueous solution in the presence of a functional auxiliary agent.
2. The 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst according to claim 1, wherein: The oxidized graphene is synthesized by Hummers method; Based on the total weight of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst, the content of Ag:ZnIn2S4 is 30-50%.
3. The 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst according to claim 1 or 2, wherein: The functional additives include L-cysteine solution and thioacetamide solution; The concentration of the L-cysteine solution is 0.05-0.15 mmol mL -1 ; The concentration of the thioacetamide solution is 0.05-0.15 mmol mL -1 ; The dosage ratio of the oxidized graphene, water, L-cysteine solution and thioacetamide solution is (90-110): (25-35): (25-30): (90-100) mg / mL / μL / μL.
4. The 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst according to claim 1, wherein: The preparation method of the composite Z-type photocatalyst comprises the following steps: S1: mixing and stirring the oxidized graphene and water in the inner lining of a reactor to obtain a first mixed solution; S2: Mixing the first mixed solution with an AgNO3 aqueous solution, a Zn(OAc)2 aqueous solution, an In(OAc)3 aqueous solution and a functional additive in the inner lining of a reactor and stirring the mixture to obtain a second mixed solution; S3: placing the reactor lining containing the second mixed liquid into the reactor shell and performing heating, cooling, washing and drying treatments in sequence to obtain the composite Z-type photocatalyst.
5. The 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst according to claim 4, wherein: The heating treatment temperature is 150-200°C and the time is 22-30h; The drying process is carried out at a temperature of 45-55°C and for a time of 10-15 hours.
6. Use of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst described in any one of claims 1 to 5 as a material for preparing an exposed layer of an exposed waterproof membrane.
7. An exposed waterproof membrane, characterized in that: The exposed waterproofing coiled material comprises a substrate and an exposed layer coated on the upper surface of the substrate; The material of the exposed layer includes sand particles and the 2DRGO / Ag:ZnIn2S4 composite Z-type photocatalyst described in any one of claims 1-5.
8. The exposed waterproof membrane according to claim 7, wherein: Based on the total weight of the material of the exposed layer, the content of the sand particles is 95.0-99.9%, and the content of the 2D RGO / Ag:ZnIn2S4 composite Z-type photocatalyst is 0.1-5.0%; The sand particles are shale flakes.
9. The exposed waterproof membrane according to claim 7, wherein: The substrate comprises a tire base and a coating layer; the tire base, coating layer and exposed layer are arranged in sequence from bottom to top; The tire base is a polyester tire base; The materials of the coating layer include the following components in parts by weight: 55-65 parts of base asphalt, 8-12 parts of SBS modifier, 3-10 parts of rubber powder filler and 15-25 parts of stone powder filler.
10. The exposed waterproof membrane according to claim 9, wherein: The coating layer is prepared by mixing and stirring the base asphalt, SBS modifier, rubber powder filler and stone powder filler evenly, and then coating the mixture on the tire base. Preferably, the stirring temperature is 150-200°C, the stirring speed is 1500-2500r / min, and the stirring time is 2-3h.